Improving Students’ Mastery on Simple Present Tense Through Climbing Grammar Mountain Game - Fadilla Taslim (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
This study aims to determine whether the use of Climbing Grammar Mountain Game gave significant improvement on students in learning simple present tense. Classroom action research was used in this study where the data were analyzed by using quantitative and qualitative approaches. The population of the study was the students of grade eleventh at SMPN 1 Luak 50 Kota. There were 21 students in this class. Six kinds of instruments were used to collect data, namely teaching ,scenario, observation sheet, questionnaire, test, interview, and teacher’s journal. This study ran for two cycles. In the second cycle, it was shown that there was gradual improvement from the previous cycle which changed from 64 (insufficient) to 79 (sufficient) of the mean score. it was more than criteria of the students’ mean score which were determined in this study and it was significant because it proved that the students enthusiasm to study simple present tense, it mean that the students liked and were not bored again so this was a motivation for them to more concentrate to study simple present tense and they could use it in daily life for communication. They understand that simple present tense is important in learning English because it is used in daily life, either in writing and spoken language. It could be concluded that Climbing Grammar Mountain Game could improve the ability of the students in class VII B of SMPN 1 Luak 50 Kota in using Simple Present Tense.